NURSES’ JOB SATISFACTION AND LEADERSHIP STYLES IN A PUBLIC HOSPITAL : A SYSTEMATIC REVIEW - Suparman Suparman; Anisah Ardiana (UPT Penerbitan Universitas Jember, 2023)
Background: A factor that might affect job satisfaction is the leadership style. The purpose of this literature review is to analyse several leadership styles and its influence on job satisfaction of nurses in hospitals. Methods: The method used is a systematic literature review incorporating two databases including Google Scholar and PubMed. Results: A total of 191 articles were identified. After the identification, screening and eligibility processes of 37 articles, there were 10 articles met the inclusion criteria. These ten articles highlight there are three leadership styles applied including transformational, transactional and laissez faire leadership. The literatures explained that leadership styles most influenced job satisfaction. The transformational leadership style is the most widely applied leadership style in hospital. Conclusions: the literature study shows that the main factor causing job dissatisfaction and job satisfaction is leadership style. The appropriate leadership style have a positive impact on increasing nurse job satisfaction. Thus, it will improve quality of nurses’ performance.